"Is the Pain a Sign of Healing?": Cancer Patients' Experiences of Energy Healing in a Pragmatic Trial. (September 2022) - Agdal, Rita
The use of complementary and alternative medicine has increased, most markedly among cancer patients. Previous research on energy healing is inconclusive, but qualitative studies have mainly reported positive healing experiences, whereas positive results from trials are scarce. Considering the apparent discrepancy between qualitative and quantitative studies, we aimed to describe the interpretation processes of the patients receiving energy healing. We followed the interpretation processes of a subsection of cancer patients who participated in a pragmatic trial on energy healing, including patients in the control groups. No significant differences between the groups were found in the quantitative part of the trial, but the majority of patients in both the intervention and control groups reported subjective improvements. A subset of 32 patients from the trial was selected for this qualitative sub-study to gain insight into their interpretation processes. These 32 patients recruited from the trial were followed with qualitative interviews before, during, and after the treatment period, using a cultural-phenomenological approach. Most patients who received energy healing changed their perception of bodily experiences, and they perceived a wider variety of signs as indicative of healing than the patients in the control groups. After receiving energy healing, the patients also perceived signs that from a medical perspective are regarded as symptoms, as signs of healing. The changes in perception of illness and healing affected decision-making dynamics and should be considered when producing information and communication strategies for health promotion.